Microcontroller-Based Speed and Overload Detection System for Public Vehicles - Indra Irwansyah; Bambang Afriansyah; Steven Christoper Girsang; Taufik Regiwista Ramadhani; Nirwan Sinuhaji; Eriansyah Saputra Hasibuan (Karya Techno Solusindo, 2025)
The entry speed sensor functions to calculate the speed of a public vehicle, and the Driver LCD display functions to confirm the information that occurs in the system, so the display and the buzzer work together so that if the buzzer sounds the information is on the display All components of the Overload and Detection System can run according to plan. The implementation of a microcontroller-based speed and overload detection system on public vehicles makes it easier for drivers to detect excess speed and overload. This tool uses an Arduino ATmega328 which functions as the main controller of the entire system so that it becomes more efficient. Effectively, this tool is also based on IoT which can emit a beep sound if the specified speed and load exceeds. This tool will convey information in the form of a warning sound produced by the Driver Buzzer. REFERENCES Arifin, N. Y., Borman, R. I., Ahmad, I., Setyaning Tyas, S., Sulistiani, H., Herdiansyah, A., & Suri, G. P. (2021). Analisa Perancangan Sistem Informasi (P. T. Cahyono, Ed.; Pertama). Yayasan Cendikia Mulia Mandiri. Effendy, E., Siregar, E. A., Fitri, P. C., & Damanik, I. A. S. (2023). MENGENAL SISTEM INFORMASI MANAJEMEN DAKWAH (PENGERTIAN SISTEM, KARAKTERISTIK SISTEM). Jurnal Pendidikan Dan Konseling, 5(2). Fahmizal, Mayub, A., Arrofiq, M., & Ruciyanti, F. (2022). Mudah Belajar Arduino dengan Pendekatan Berbasis Fritzing, Tinkercad dan Proteus (Pertama). Deepublish. FIRMANSYAH, T., RIYANDIKA, R., SARASWATI, I., SUPRIYANTO, WILDAN, MUH., SUPRIYANTO, T., & ALAM, S. (2023). Rancang Bangun Doppler X-Band Speed Detector untuk Kendaraan Roda Dua pada Jalan Kelas IIIC. ELKOMIKA: Jurnal Teknik Energi Elektrik, Teknik Telekomunikasi, & Teknik Elektronika, 11(2). Firmawati, N., Farokhi, G., & Wildian, W. (2019). Rancang Bangun Mesin Pembuat Minuman Kopi Otomatis Berbasis Arduino UNO dengan Kontrol Android. JITCE (Journal of Information Technology and Computer Engineering), 3(01), 25–29. https://doi.org/10.25077/jitce.3.01.25-29.2019 Khakim, L. (2023). Buku Ajar Mikrokontroler ATMega 328 (Moh. Nasrudin, Ed.; Pertama). PT. Nasya Expanding Management. Muttaqin, I. R., & Santoso, D. B. (2021). Prototype Pagar Otomatis Berbasis Arduino Uno Dengan Sensor Ultrasonic Hc-SR04. JE-Unisla, 6(2), 41. https://doi.org/10.30736/je-unisla.v6i2.695 Perdana, I. G. I., Wibowo, H., & Ridwan, A. (2021). PENGUKURAN KECEPATAN KENDARAAN BERBASIS MIKROKONTROLER GUNA MENUNJANG KESELAMATAN DALAM BERKENDARAN. Jurnal Penelitian, 6(4). Rinaldi, N., Lestari, F., & Pramita, G. (2022). Identifikasi Kerusakan Jalan dan Alternatif Perbaikan Jalan Pada Ruas Jalan Tegineneng – Gunung Sugih Lampung. Jurnal Teknika Sains, 7(1). Satura, F. R., Chandra, A. A., & Adhinata, F. D. (2021). Pengukur Kecepatan Kendaraan Menggunakan Algoritma Image Subtracting. Journals of Information, Control, Telecommunication and Electrical, 2(2). Sholihin, M., Wibowo, S. A., & Prasetya, R. P. (2021). PENERAPAN IoT (INTERNET of THINGS) TERHADAP RANCANG BANGUN SISTEM PERINGATAN BATASAN KECEPATAN DAN PENDETEKSI LOKASI KECELAKAAN BAGI PENGENDARA SEPEDA MOTOR BERBASIS ARDUINO. JATI (Jurnal Mahasiswa Teknik Informatika), 5(2). Wicaksono, A. (2019). Buku Ajar Microprocessor (S. B. Sartika & M. Tanzil Multazam, Eds.). UMSIDA Press. YOGASARA, D. F. (2023). SISTEM INSTRUMENTASI IOT BERBASIS LOAD CELL UNTUK PEMANTAUAN KESETIMBANGAN BEBAN MUATAN DI KERETA API. Universitas Telkom.